THE IMPLEMENTATION OF CSR REPORT BASED ON TRIPLE BOTTOM LINE AND ISO 26000 (Case Study PT. Astra Tbk.) - Wicaksono, M. Satriyo; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The study tries to analyses the implementation of corporate social responsibility (CSR) in PT Astra Tbk by using triple bottom line combined with ISO 26000. The author uses content analyses method. By using content analysis, it can be seen whether the CSR report made by PT Astra Tbk is in accordance with ISO 26000 or not. In fact, the results from the content analysis of CSR activity show that most of PT Astra Tbk activities have already been suitable with the indicator in ISO 26000, such as: organizational governance, labor practice, human right, customer issue, community development and environment issue. There are some indicators, however in the fair operating practices which are not published by this company in its indicator report of ISO 26000, such as anti corruption, fair operating practice, responsible political involvement and respect for property right. Â Key word: corporate social responsibility (CSR), triple bottom line, ISO 26000, secondary data, content analysis.